Passing through or journey's end? A chronological analysis of projectile point curation and discard at Rollins Pass, northern Colorado - Dinkel, Michelle A., author; LaBelle, Jason M., advisor; Glantz, Michelle M., committee member; Jacobi, Tobi, committee member (Colorado State University. Libraries, 2021)
Rollins Pass is an intermountain travel corridor situated along the Continental Divide that connects the Western Slope and the Front Range of Colorado. This high-altitude pass is located at the intersection of Gilpin, Boulder, and Grand counties, and is notable because it contains the highest density of pre-contact Native American alpine game drives in North America. While the game-drive features represent one aspect of prehistoric use, 17 sites, four small sites, and five isolated finds provide an opportunity to explore a different facet of the prehistoric use of Rollins Pass. Investigations at these surface sites and isolates produced a total of 91 projectile points. Past research conducted at high altitudes in northern Colorado suggests prehistoric use spans from the Paleoindian to the Protohistoric period. However, chronological reconstruction is challenging in alpine settings due to poor preservation, shallow stratigraphy, and short occupation spans by hunter-gatherer groups. Due to this complication, researchers often rely on typology or index fossils, such as projectile points, to assign age to surface sites. While the analysis of other chipped stone data can provide information on-site use and occupation span, it is frequently complicated by the occurrence of multicomponent or palimpsest sites. This thesis aims to examine the prehistoric use of Rollins Pass through the analysis of projectile points -- a functional tool type -- to establish chronology, lithic raw material use, and curation intensity. The results suggest an occupation beginning in the Late Paleoindian period and extending to at least the Middle Ceramic era (10,000 - 410 BP). Lithic raw materials identified suggest consistent acquisition of both local and non-local toolstone, across all periods represented. Curation patterns demonstrate a willingness to discard high utility portions of tools, with many projectile points discarded despite a potential to rejuvenate their forms and indicating a lack of raw material conservation. Projectile point analysis of Rollins Pass sites and isolates suggest that prehistoric hunter-gatherer populations interacted with the pass as a destination and to lesser extent as an intermountain travel corridor.
Keywords: discard; northern Colorado; projectile point; high-altitude; curation; prehistoric archaeology